Softcell constraints for robust real-time deformation - Teo, Edmund Yew Kuan (2009)
This thesis presents softcell constraints, a novel set of formulations for robust real-time deformation. The underlying model handles volumetric objects in the form of surface mesh. The main theory behind the approach is to voxelize the surface mesh into cuboid cells. Neighbouring cells are elastically coupled together through constraint forces and torques. Based on geometric formulations, the constraint forces/torques are designed to minimize the global elastic energy. The rigidity of the cells is inspired by the coupled prisms method and has made the method highly robust even when under extreme deformation. The simulation cost is linear to the number of cells. Thus, it is capable of handling a reasonable number of complex objects. Collisions are easy to handle as it is based on cuboid primitives. Thus, it eliminates the burden to implement complex collision detection technique and contact handling. This combination of robustness, performance and ease of implementation makes the method particularly interesting for games.